TINGKAT LITERASI KEUANGAN DAN FINANCIAL TECHNOLOGY PADA PELAKU USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) KABUPATEN KUNINGAN - Amir Hamzah; Dadang Suhardi (Universitas Pakuan, 2020)
The purpose of this study is to examine the level of financial literacy and financial technology of SMEs in Kuningan Regency. The sample of this study were 250 SMEs. Sampling is done by Probability sampling with proportional random sampling technique. The data analysis method with Structural Equation Modeling (SEM). From the results of the study it was found that financial attitude has positive effect on financial technology, financial behavior has positive effect on financial technology, financial knowledge has positive effect on financial technology, financial technology has positive effect on financial inclusion.Thus, in order to achieve the level of financial literacy and financial technology in SMEs increases, SMEs must pay attention to the level of financial attitude, financial behavior, financial knowledge, financial technology so that SMEs financial inclusion also increases.